Role of Proprioception in Slow and Rapid Movements. Issue 2 (April 2020) - Feng, Jie; Hung, Tsung-Min; Huang, Rui; Hou, Shuang; Ren, Jie
This study aimed to compare the contributions of sources of proprioception to the reproduction accuracy of relatively slower and more rapid arm movements. We recruited 34 volunteers and gave them dart throwing tasks under two different durations followed by joint position sense (JPS) tests and force sense (FS) tests at the elbow and the wrist. We found moderately positive correlations between slow movement performance and proprioceptive acuity with FS (wrist) and JPS (elbow), accounting for 52% of the absolute errors ( p < .001), and, with FS (wrist), accounting for 50% of the variable error ( p < .001). Moreover, we observed a smaller correlation between rapid movement performance and proprioceptive acuity, accounting for 17% of absolute errors with JPS (elbow; p = .008) and 11% of variable error ( p = .033). These results suggest that relatively slow movement performance is partly determined by performers' proprioceptive acuity of the movement-related limbs. Relatively rapid movement performance is also affected by correctional proprioceptive feedback, though to a lesser degree.